Availability and Effectiveness of Differential Navigation Satellite System (DGNSS) Radio Beacon for Hydrographic Positioning - Rozaimi, Che Hasan; Mohd, Razali Mahmud (Penerbit Universiti Sains Malaysia, 2004)
Differential Global Navigation Satellite System (DGNSS) radio beacon has been recognized in most country as an aid to safety for marine navigation. The International Association of Marine Aids to Navigation and Lighthouse Authorities (IALA) has listed all DGNSS stations that have officially operated around the world. The authorized frequency for DGNSS radio beacon is between 283.5 kHz to 325 kHz. In this way, users are able to receive DGPS correction through Radio Technical Commission for Maritime Services Special Committee 104 (RTCM SC-104) format (IALA, 2001).